In order to find the value of the composition of 2
functions, in our case f and g, we have to follow the
steps:
Step 1: First, we have to find out the expression of
the composition of the 2 functions:
(f*g)(x) =
f(g(x))
To find f(g(x)) we have to substitute x by g(x) in
the expression of f(x):
f(g(x)) =
2*(g(x))-6
Now, we'll substitute g(x) by it's
expression:
2*g(x)-6 = 2*(9x^2-7x-4) -
6
We'll open the
brackets:
2*(9x^2-7x-4) - 6 = 2*9x^2 - 2*7x - 2*4 -
6
f(g(x)) = 18x^2 - 14x -
14
Step 2:
Now, we'll
calculate the value (f*g)(-6), substituting x from the expression of (f*g)(x), by
(-6).
(f*g)(-6) = 18(-6)^2 - 14(-6) -
14
(f*g)(-6) = 648 + 84 -
14
(f*g)(-6) =
718
No comments:
Post a Comment